2019
DOI: 10.1029/2019gl084162
|View full text |Cite
|
Sign up to set email alerts
|

Major Contribution of Reduced Upper Ocean Oxygen Mixing to Global Ocean Deoxygenation in an Earth System Model

Abstract: We present a quantitative analysis of deoxygenation drivers applied to an Earth System Model and easily transposable to large model ensembles. The preindustrial ocean breathes in oxygen in polar regions and in subtropical gyres, and breathes out oxygen in the equatorial band and in subpolar gyres. Under a high‐CO2 emission scenario for the 21st century, small deviations of these large natural oxygen fluxes cause global deoxygenation. We attribute half of this trend to a decrease in oxygen solubility. The other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Waters with low oxygen saturation are particularly sensitive to impacts of climate warming (Fu et al, 2018) as well as vertical diffusivity that is parameterized by the mixing coefficient in the models (Duteil et al, 2012) and also mesoscale eddy transport and the lateral mixing coefficient (Bahl et al, 2019;Lachkar et al, 2016). Globally, reduced mixing across the mixed layer explains 75 % of the reduced subduction, but regionally changes in wind patterns that cause modulations in Ekman pumping and subduction are more important (Couespel et al, 2019). Thus, future trends in the northern Indian Ocean OMZs derived from the ESMs are highly uncertain, with projected potential increases or decreases in the volume of low-oxygen waters, depending on the model and the oxygen levels under consideration (Bopp et al, 2013;Cocco et al, 2013).…”
Section: Future Projectionsmentioning
confidence: 99%
“…Waters with low oxygen saturation are particularly sensitive to impacts of climate warming (Fu et al, 2018) as well as vertical diffusivity that is parameterized by the mixing coefficient in the models (Duteil et al, 2012) and also mesoscale eddy transport and the lateral mixing coefficient (Bahl et al, 2019;Lachkar et al, 2016). Globally, reduced mixing across the mixed layer explains 75 % of the reduced subduction, but regionally changes in wind patterns that cause modulations in Ekman pumping and subduction are more important (Couespel et al, 2019). Thus, future trends in the northern Indian Ocean OMZs derived from the ESMs are highly uncertain, with projected potential increases or decreases in the volume of low-oxygen waters, depending on the model and the oxygen levels under consideration (Bopp et al, 2013;Cocco et al, 2013).…”
Section: Future Projectionsmentioning
confidence: 99%
“…A marked intensification, expansion, and shoaling of OMZs has been detected in recent decades (Bograd et al., 2008; Breitburg et al., 2018; Emerson et al., 2004; Stramma et al., 2008), although considerable uncertainty remains in distinguishing long‐term trends from multidecadal cycles (Stramma et al., 2012). Under a global warming scenario, propositions or predictions have been made about an expansion of OMZs due to mechanisms involving changes in oxygen solubility, ventilation of the deep ocean, and/or biological oxygen consumption or respiration (see Couespel et al., 2019; Keeling et al., 2010; Matear & Hirst, 2003; Oschlies et al., 2018; Schmidtko et al., 2017; Shaffer et al., 2009). The expansion may persist for at least several centuries even after atmospheric carbon dioxide stops rising (Yamamoto et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…global warming scenario, propositions or predictions have been made about an expansion of OMZs due to mechanisms involving changes in oxygen solubility, ventilation of the deep ocean, and/or biological oxygen consumption or respiration (see Couespel et al, 2019;Keeling et al, 2010;Matear & Hirst, 2003;Oschlies et al, 2018;Schmidtko et al, 2017;Shaffer et al, 2009). The expansion may persist for at least several centuries even after atmospheric carbon dioxide stops rising (Yamamoto et al, 2015).…”
mentioning
confidence: 99%
“…(ii) Although k v has been thoroughly assessed in this study, it only considers the tidal mixing, and it does not account for convective-driven mixing at the base of the ML during winter (Kolodziejczyk & Gaillard, 2013;Yeager & Large, 2007), so it is likely underestimated. The role of tidally driven mixing in shaping the concentration of passive tracers in the open ocean has recently been highlighted by Tuerena et al (2019), and the negative oxygen diffusion trend was found to be the dominant contributor of the predicted ocean deoxygenation over this century (Couespel et al, 2019).…”
Section: 1029/2020gl089040mentioning
confidence: 98%